When Will the Lockdown End? Confinement Duration Forecasts and Self-Reported Life Satisfaction in Spain: A Longitudinal Study - Sabater-Grande, Gerardo; García-Gallego, Aurora; Georgantzís, Nikolaos; Herranz-Zarzoso, Noemí (Frontiers in Psychology, 2021)
This paper reports results from a longitudinal study on the impact of the lockdown on daily self-reported life satisfaction levels during the first wave of the COVID-19 pandemic in Spain. A stable panel (N=1,131) of adult subjects were surveyed during the period March 29-June 20, 2020. They were asked to report daily life satisfaction and health state levels. Interestingly, daily satisfaction with life increased during the lockdown. At the beginning of the experiment, subjects were asked to guess the end-week of the lockdown, against a possible monetary reward for accurate forecasts. Subjects predicting a longer lockdown period reported a higher average level of daily life satisfaction. Females reported on average lower levels of daily life satisfaction, but exhibited a stronger tendency to report higher levels of life satisfaction, the longer the lockdown forecast. Individual heterogeneity in life satisfaction levels can be partly attributed to personality traits, with neuroticism having a negative effect, while extraversion and agreeableness having a positive effect on daily life satisfaction.